2020
DOI: 10.3390/w12092579
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations of Dissolved Iron Concentration in Active Layer and Rivers in Permafrost Areas, Russian Far East

Abstract: Dissolved iron (dFe) in boreal rivers may play an important role in primary production in high-latitude oceans. However, iron behavior in soils and dFe discharge mechanism from soil to the rivers are poorly understood. To better understand iron dynamics on the watershed scale, we observed the seasonal changes in dFe and Dissolved Organic Carbon (DOC) concentrations in the river as well as dFe concentration in soil pore waters in permafrost watershed from May to October. During snowmelt season, high dFe product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
1
16
1
Order By: Relevance
“…High-latitude river systems transfer large amounts of dissolved iron, that is, iron-bearing humic substances (SAHLs) from land to sea. These unique substances have been shown to contribute significantly to relieving iron deficiency in coastal regions and shelf seas as well as in surface waters of the open Arctic Ocean and the northern North Atlantic Ocean, thereby supporting the oceanic sink for anthropogenic CO 2 . ,, …”
Section: Discussionmentioning
confidence: 99%
“…High-latitude river systems transfer large amounts of dissolved iron, that is, iron-bearing humic substances (SAHLs) from land to sea. These unique substances have been shown to contribute significantly to relieving iron deficiency in coastal regions and shelf seas as well as in surface waters of the open Arctic Ocean and the northern North Atlantic Ocean, thereby supporting the oceanic sink for anthropogenic CO 2 . ,, …”
Section: Discussionmentioning
confidence: 99%
“…Given the high correlation coe cients between annual/late summer dFe concentration and Ta with a lag of 8 years, we infer that increased dFe discharge likely lasted for 1-2 years. In addition to input of groundwater rich in dFe, summer rainfall is also considered to increase dFe concentration in rivers 17,49 . However, there was no signi cant correlation between the individual measurements of the Amur River discharge and dFe concentration in late summer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…active layer thickness peaks in September 17 . Dissolved iron was measured by the colorimetric method with 1,10-phenantroline, which was applied to water ltered through Whatman GF/F lters (0.7 µm) and acidi ed to pH < 2 with HCl (Russian international technical standards 52.24.358-2006) 57 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the knowledge of river water chemical composition in Siberia, Tashiro et al [4] studied watershed-scale iron dynamics, and coupled the seasonal changes in Fe and dissolved organic carbon (DOC) concentrations in the tributaries of the Amur River basin. They demonstrated that permafrost wetlands in valley areas act as hotspots of dissolved Fe production and greatly contribute to Fe and DOC discharge to rivers, especially during snowmelt and rainy seasons.…”
mentioning
confidence: 99%